The implementation of continuing professional development of economics teachers at state senior high schools in semarang: investigating the constraints and challenges - Budiyono, Budiyono (Dinamika Pendidikan, 2016)
This research aims to analyze and investigate: (1) the extent in which the implementation of Continuing Professional Development of Economics Teachers at State Senior High Schools in Semarang; (2) barriers in implementing this program; (3) challenges in the futures when applying this program. This study is a descriptive qualitative research. Data were collected by questionnaires and interviews to teachers. There were around 27 economics teachers in Semarang as the subjects of this research. The results show that personal development by individual teacher and group of teachers in the teacherâs association are more likely to be performed than personal development at a peer group. The major problem in this continuous development is the strict teaching hour. Moreover, the key challenges in the improvement of teaching profession is the way to optimize the role of teachersâ association and the availability of information technology in aiming sustainable professional development.Tujuan penelitian ini untuk menganalisis dan menginvestigasi 1) sejauh mana implementasi program Pengembangan Keprofesionalan Guru Berkelanjutan (PKGB) pada Guru Ekonomi Wilayah Semarang; 2) hambatan pelaksanaan program PKGB pada Guru Ekonomi SMA Negeri Wilayah Semarang; 3) tantangan ke depan pelaksanaan PKGB pada Guru Ekonomi Wilayah Semarang. Penelitian ini adalah penelitian deskriptif kualitatif. Teknik pengumpulan data akan dilkukan dengan menggunakan kuesioner dan wawancara kepada guru. Adapun subyek penelitian ini adalah guru ekonomi wilayah Semarang yang berjumlah 27 orang. Hasil penelitian menunjukkan secara individu pengembangan dilakukan kadang-kadang oleh guru, secara peer sesama guru bidang ekonomi jarang dilakukan sedangkan secara berkelompok melalui Musyawarah Guru Mata Pelajaran juga dilakukan kadang-kadang. Hambatan utama yang dihadapi oleh guru dalam pengembangan keprofesionalan berkelanjutan adalah jam mengajar yang sangat padat. Tantangan yang ada dalam pengembangan profesi guru adalah bagaimana mengoptimalkan peranan MGMP, dan ketersediaan teknologi informasi guna pengembangan keprofesionalan berkelanjutan.